DESAIN RANCANGAN GANTRY: DESAIN RANCANGAN GANTRY CNC ROUTER 3 AXIS DENGAN PENDEKATAN TOPOLOGY - M. Nushron Ali Mukhtar; Mochamad Andi Akrianto (ELEMEN : JURNAL TEKNIK MESIN, 2022)
The 3 Axis Gantry CNC Router Design uses the finite element method as an essential step, bearing in mind that the shape displacement caused by the chisel movement must be as minimal as possible because it affects the quality of the craft. This study aims to optimize the gantry design of a three-axis CNC Router machine that is strong, light, and sturdy. This study uses the Finite Element Method with a topological approach to solving engineering problems. The results of the data analysis are in the form of von Mises, displacement, and safety factor values from the simulation of 10 kg, 20 kg, and 30 kg loading variations. Furthermore, optimization is carried out on the design of the gantry design using topological analysis to reduce the weight or mass of the gantry construction. The results of the modified gantry design are more optimal than the new and initial gantry designs, both from the effects of von Mises, displacement, and safety factors. In addition, the weight or mass of the modified gantry design is lighter by 1.8 kg.